Produk Metabolisme Rumen pada Sapi Peranakan Ongole Fase Tumbuh - S.N.O. Suwandyastuti (Agricultural Faculty, 2013)
Rumen metabolism product on growing cattle ongole gradeABSTRACT. The utilization of fermented fibrous waste material had improved the product of rumen metabolism in vitro, nevertheless, it was not always the same result if treated on animal, in vivo. An experiment had been conducted to investigate the result of the in vitro trial to the growing male cattle of Ongole Grade. The experiment had been conducted by experimental method using twelve (12) growing male cattle of Ongole Grade. The trial was conducted in Completely Randomized Block Design, during seven months period, three months adaption, two weeks preliminary, three months feeding trial and two weeks digestion trial. The treatment tested were: R0 = control ration, non fermented; R1 = mesh type fermented and R2 = pellet type fermented. The variables measured were: the production of Total Volatile Fatty Acid (T-VFA); asetate (C2), propionate (C3), butyrate (C4). The result shown that the treatment, biological and physical, of complete feed, does not influence on the production of T-VFA as well as on the composition (C2, C3 and C4). Nevertheless based on all the variables measured, the biological treatment with fermentation tends to increase the production of rumen metabolism, and the highest result of the products of T-VFA = 112,43 + 17,2 mM/L, C2 = 40,46 + 8,98 mM/L, C3 = 34,57 + 7,35 mM/L, C4 = 31,17 + 7,35 mM/L, were resulted from pellet type of complete feed. The result of experiment concludes : (1) based on the production of VFA as well as its composition, and the balance of C2 / C3, the utilization of complete feed both mesh and pellet type increases the efficiency of energy utilization on the growing male of Ongole Grade Cattle; (2) based on rumen metabolism product, the recommended complete feed for growing male cattle of Ongole grade is in the form of fermented pellet.